Movement disorders in patients with schizophrenia and a history of substance abuse. (27th March 2013) - Hansen, Lars K.; Nausheen, Bina; Hart, Deborah; Kingdon, David
Abstract : Objective: The movement disorders acute dystonia, akathisia, Parkinsonian symptoms and tardive dyskinesia [extrapyramidal side effects (EPSs)] are recognized adverse effects of antipsychotic medication. Previous studies have indicated that substance abuse in patients with schizophrenia can worsen EPS. This study therefore investigated the relationship between drug and alcohol use and EPS in a group of patients with schizophrenia. Methods: Seventy patients with schizophrenia assessed for drug and alcohol use, global functioning, EPS and suicidality. Chlorpromazine equivalents were correlated to levels of EPS and substance abuse. Results: Current EPS were found in 65% of the sample despite three‐quarters of the patients receiving second‐generation antipsychotics. An even higher level of patients, 87%, was found to have a history of EPS. A long history of schizophrenia independently predicted presence of any EPS, particularly akathisia, controlling for history of substance abuse which was a non‐significant predictor. Conclusions: History or current use of alcohol or drug abuse did not predict EPS, except for alcohol abuse at the time of diagnosis which was associated with current akathisia. Length of illness was correlated with EPS, whereas suicidality was not linked to akathisia. Neither chlorpromazine equivalent antipsychotic dose nor whether the patient received first‐generation or second‐generation antipsychotic medication was significantly associated with EPS or substance abuse. Copyright © 2013 John Wiley & Sons, Ltd.